If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 4 + x = 6 + 3 Combine like terms: 5 + 4 = 9 9 + x = 6 + 3 Combine like terms: 6 + 3 = 9 9 + x = 9 Add '-9' to each side of the equation. 9 + -9 + x = 9 + -9 Combine like terms: 9 + -9 = 0 0 + x = 9 + -9 x = 9 + -9 Combine like terms: 9 + -9 = 0 x = 0 Solving x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Simplifying x = 0
| 8x-18=5x-21 | | 2n-1=4n-2(n+1) | | a-[2a-[b-(3a-2b)]]=0 | | y=2x+54 | | (x+2)+2x+(2x+8)=180 | | 5(4+2x)=-10 | | 4c+19+3c=-30 | | 2.5y=7.5 | | 19.4-0.5t=19.61 | | x-23/-12=22 | | 56x-49y+35= | | 2(5m-8)=4m+2(3m-8) | | -8+2x+2x-9=19 | | 12hX$5/h= | | X/49 | | 5[3+5+2a]=30 | | a-[2a-[b-(3a-2a)]]=0 | | s^2/24=50 | | d-2.5=-14.1 | | 11.5y+16.1=20.7 | | .6(3x+6)=1.1-(x+2) | | 4(2f+3)=3f-23 | | 1.5n+2=2.9 | | b+8b-2b-10b=-17 | | 6(2y-7)=12y+10 | | 3[23-2b]+3b=48 | | tan^2x-2tanx+1=0 | | 4(1-x)+3x=-2-2 | | x/8-4/3=1 | | 8=h | | 14n=2(6n-9) | | 6xsquare-12=0 |